Transfusion-free Strategies in Liver and Pancreatic Surgery: A Predictive Model of Blood Conservation for Transfusion Avoidance in Mainstream Populations. Issue 3 (17th March 2023) - Kulkarni, Sujit; Parina, Ralitza; Henderson, Randy; Derek, Elika; Selby, Taylor; Kwon, Yong; Emamaullee, Juliet; Sher, Linda; Genyk, Yuri; Selby, Rick
Abstract : Objective: The objective of this study is to (1) describe the techniques and prove the feasibility of performing complex hepatobiliary and pancreatic surgery on a Jehovah Witness (JW) population.  (2) Describe a strategy that offsets surgical blood loss by the manipulation of circulating blood volume to create reserve whole blood upon anesthesia induction. Background: Major liver and pancreatic resections often require operative transfusions. This limits surgical options for patients who do not accept major blood component transfusions. There is also growing recognition of the negative impact of allogenic blood transfusions. Methods: A 23-year, single-center, retrospective review of JW patients undergoing liver and pancreatic resections was performed. We describe perioperative management and patient outcomes. Acute normovolemic hemodilution (ANH) is proposed as an important strategy for offsetting blood losses and preventing the need for blood transfusion. A quantitative mathematical formula is developed to provide guidance for its use. Results: One hundred one major resections were analyzed (liver n=57, pancreas n=44). ANH was utilized in 72 patients (liver n=38, pancreas n=34) with median removal of 2 units that were returned for hemorrhage as needed or at the completion of operation. There were no perioperative mortalities. Morbidity classified as Clavien grade 3 or higher occurred in 7.0% of liver resection and 15.9% of pancreatic resection patients. Conclusions: Deliberate perioperative management makes transfusion-free liver and pancreatic resections feasible. Intraoperative whole blood removal with ANH specifically preserves red cell mass, platelets, and coagulation factors for timely reinfusion. Application of the described JW transfusion-free strategy to a broader general population could lessen blood utilization costs and morbidities.